MODEL PEMBELAJARAN TEMATIK PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Umu salamah (Jurnal Pendidikan Agama Islam, 2014)
Thematic approach to teaching and learning especially for Islamic Religious Education in elementary school. This is a way of teaching and learning, whereby many areas of the curriculum are connected together and integrated within a theme. It allows learning to be more natural and less fragmented than the way, where a school day is time divided into different subject areas and whereby children practice exercises frequently related to nothing other than what the teacher thinks up. It guides connected ideas to follow on easily.The model of thematic learning in primary schools can be said to be using the model to share (shared/participative model). This modelis the integration of learning due to the emergence of a fallen-overlapping (overlapping concept) or an idea in two or more subjects.